effectiveness of oxytocin and breast massage on prolactin level and breast milk production among postpartum mothers at tertiary level hospital, eastern Nepal. - BC,Sushmita (2020)
ABSTRACT: Background: Breastfeeding is considered as one of the most natural and intimate of all human interactions. Breast milk production is affected by prolactin and oxytocin(let down) hormones, which play role in the smooth production of breast milk. Objective: To assess the effectiveness of oxytocin and breast massage on prolactin level and breast milk production in blood among primiparous postpartum cesarean mothers. Methods: A quasi-experimental equivalent pre and posttest research design were conducted at the postnatal ward of BPKIHS, Nepal, including 30 primiparous postpartum cesarean mothers. An interview questionnaire and an observation performa prepared were used for data collection. Prolactin hormone in blood was measured by the CLIA method, breast milk, breast milk production measured based on the indicators of the duration of feeding in minutes and sleeping hours of the baby after breastfeeding ( one time in the morning), frequency of feeding, urination and defecation of the baby in 24hrs. Data were analyzed by paired t-test and independent t-test. Result: The mean difference of prolactin hormone level in experimental group was 147.216+-78.846 ng/ml while in control group was experimental and control group in prolactin significant differences between experimental and control group in prolactin level(p-value 0.001). duration of breastfeeding p value were 0.560,0.299,0.003, duration of sleeping hours after breast feeding p value 0.156,0.003,0.027, Frequency of breast feeding in 24hrs p values 0.267,0.004, 0.025 frequency of urination in 24hrs p values were 0.111, 0.02,0.001,Frequency of defecation in 24hrs p values were 0405,0.001 and 0.017 on day 1,day 2, day 3 respectively. Conclusion: The study suggests that oxytocin and breast massage is safe, effective, lack adverse effects,non expensive and nonivasive methods to increase prolactin level and improve breast milk production. Keywords: Oxytocin and breast massage , prolactin level, Breast milk production, Primparous cesarean.